Sistem Smart Trash Pemilah Sampah Organik dan Anorganik Berbasis Internet of Things - Ismail, Ismail; Nusri, Andi Zulkifli; Rahman, Syariful (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
Traditional trash bins have an impact on the accumulation of waste and the mixing of organic and inorganic waste so that it can damage the environment. This research aims to make it easier to sort organic and inorganic organic waste with three stages, namely Hardware design, program creation, and tool testing. Arduino microcontroller, Node MCU ESP8266. The ultrasonic sensor reads the presence of object in front of the sensor then servo opens the trash can lid, and the garbage is put in the trash can. The capacitive proximity sensor reads the type of garbage if the garbage is organic the servo will rotate 900 to the left and vice versa if the garbage is inorganic type the servo will rotate 1800 to the right. The smart trash system is equipped with a sensor monitoring the contents of the trash can, if the trash can is full, system sends a message to the officer. The system development method uses the SDLC method and the tool testing method uses the Black Box method. Based on the results of system testing with five trials, the average accuracy value is 96%. The contribution of this research provides new innovations in managing waste automatically.